Yearbook of the European Convention on Human Rights/Annuaire de la convention europeenne des droits de l'homme, Volume 38 A (Human Rights and Humanitarian Law - Book Archive pre-2000., 1997)
In order to further scientific knowledge of human rights, the Council of Europe holds high-level meetings, such as colloquies, round tables and seminars. Every five years an important Colloquy on the European Convention on Human Rights takes place in a town of a member State. The Eighth International Colloquy on the European Convention on Human Rights, organised by the Secretariat General of the Council of Europe in collaboration with the Ministry of Justice of Hungary and the Hungarian Institute for Legal and Administrative Sciences, was held in Budapest from 20 to 23 September 1995. This volume contains the Proceedings of the Budapest Colloquy, which covered the following themes: The European Convention on Human Rights and cultural rights 1st session: Cultural rights: universal, indivisible, and legally enforceable rights; 2nd session: Cultural rights and the management of particular situations to ensure democratic security in Europe; The European Convention on Human Rights in the new architecture of Europe 3rd session: Effects on the European Convention on Human Rights of the enlargement of the number of Contracting Parties; 4th session: Implementation of the reform of the European Convention on Human Rights control machinery. Afin de promouvoir le progrès des connaissances scientifiques en matières de droits de l'homme, le Conseil de l'Europe tient des réunions au plus haut niveau, sous forme de colloques, tables rondes et séminaires. Tous les cinq ans, un important colloque sur la Convention européenne des droits de l'homme est organisé dans une ville d'un pays membre. Le huitième Colloque international sur la Convention européenne des droits de l'homme, organisé par le Secrétariat Général du Conseil de l'Europe en collaboration avec le Ministère de la Justice et l'Institut des Sciences juridiques et administratives de Hongrie, a eu lieu à Budapest du 20 au 23 septembre 1995. La présente publication contient les actes du huitième Colloque. Le Colloque portait sur les thèmes suivants: La Convention européenne des droits de l'homme et les droits culturels 1e session: Les droits culturels: droits individuels universels, indivisibles, et justiciables; 2e session: Les droits culturels et le traitement de situations particulières en vue d'assurer la sécurité démocratique en Europe; La Convention européenne des droits de l'homme dans la nouvelle architecture de l'Europe 3e session: Les effets de l'accroissement du nombre des Parties contractantes sur la Convention européenne des droits de l'homme; 4e session: La mise en oeuvre de la rérme du mécanisme de contrôle de la Convention européenne des droits de l'homme.